2002
DOI: 10.1007/s00113-001-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiusköpfchentrümmerfrakturen Erste Erfahrungen mit der Radiusköpfchenprothese von Judet

Abstract: Compared with resection or Swanson-prothesis the bipolar prothesis of Judet has definite advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
6

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
6
0
6
Order By: Relevance
“…8 The observations of Popovic et al have to be interpreted differently, as the authors presumed that only the radiolucent lines that were already visible within the first postoperative year and remained stable overtime are the result of an insufficient cementing technique, and that the progressive radiolucent lines and proximal bone resorption occur due to mechanical factors and wear debris. Because these findings were not noted in any of the numerous short-term studies, 3,12,32,34 nor in Muller's, Dotzis', or Frosch's 5-year studies, 7,9,23 nor in our 8.8-year results of Judet's bipolar radial head prosthesis, one must assume that all these radiologic findings may be the result of an initial insufficient cementing technique, perhaps worsened by mechanical factors and/or wear debris over the years.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…8 The observations of Popovic et al have to be interpreted differently, as the authors presumed that only the radiolucent lines that were already visible within the first postoperative year and remained stable overtime are the result of an insufficient cementing technique, and that the progressive radiolucent lines and proximal bone resorption occur due to mechanical factors and wear debris. Because these findings were not noted in any of the numerous short-term studies, 3,12,32,34 nor in Muller's, Dotzis', or Frosch's 5-year studies, 7,9,23 nor in our 8.8-year results of Judet's bipolar radial head prosthesis, one must assume that all these radiologic findings may be the result of an initial insufficient cementing technique, perhaps worsened by mechanical factors and/or wear debris over the years.…”
Section: Discussionmentioning
confidence: 46%
“…1,5,19,25 It has, therefore, superseded radial head resection as the treatment of choice for unreconstructable radial head fractures. 19,24,31 In many studies, encouraging short-term results have been reported for monobloc as well as bipolar implants 3,[7][8][9]12,17,18,21,23,27,32,34 ; but, there still exists a lack of information concerning long-term results.…”
Section: Discussionmentioning
confidence: 96%
“…) Several studies have shown good short-to midterm results of metal radial head prostheses. 1,4,6,7,8,10,11,15,18,19,28,31 However, only scarce data are available for their long-term outcome. 9 There is concern about the potential for long-term cartilage wear.…”
mentioning
confidence: 99%
“…Das Patientenkollektiv zeigte weder ein andauerndes Instabilitätsgefühl noch einen Cubitus valgus, eine Demineralisierung, eine Arthrose am Capitulum humeri oder Beschwerden im Handgelenk. Während der Einsatz bei Begleitverletzungen wie ulnarer Bandinstabilität und/oder Frakturen (Mason IV) anerkannt ist [8,9], sehen wir -wie Judet et al [12] -aufgrund der sehr guten und guten subjektiven Ergebnisse sowie der niedrigen intra-und postoperativen Komplikationsrate darü-ber hinaus die Indikation zur Implantation bei Monoverletzungen des Speichenkopfs (Mason III). …”
unclassified
“…Im Anschluss daran wird die Markhöhle gespült Abb. 9 9 Die Osteotomiefläche wird mit dem Pilotfräser reguliert, sodass eine Kongruenz zwischen dem Prothesenhals und der Resektionsfläche hergestellt wird (a). Das diaphysä-re Bett des Implantats wird mit Reibahlen zunehmender Größe vorbereitet (b).…”
unclassified